PENGARUH KUALITAS LAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN PENGGUNA (KEARSIPAN DAN PERPUSTAKAAN KAB. PUNCAK JAYA) - maniawasi, krestina; rusno; nu graha, andi (Jurnal Riset Mahasiswa Manajemen, 2024)
Abstract This research aims to determine the effect of service quality and employee performance on user satisfaction. This research uses quantitative methods, using probability sampling techniques, namely 104 visitors to the Dinas Kearsipan dan Perpustakaan Kab.Puncak Jaya. The data analysis used is multiple linear regression. The research results show that service quality and employee performance can increase user satisfaction, service quality can increase user satisfaction, employee performance can increase user satisfaction. Suggestions to increase user satisfaction need to pay attention to product quality with books neatly arranged in bookshelves.